(untitled) (Salud, Arte y Cuidado, 2026)
Objective: To identify the most relevant factors contributing to absenteeism as perceived by nursing technicians at a Brazilian regional reference hospital. Methodology: A cross-sectional case study was conducted with 284 nursing technicians from this hospital. The Absenteeism Factors at Work Scale was used, and both the overall average and the averages for the scale’s four dimensions were calculated. Results: The main causes of absenteeism were fatigue (score = 2.63), low pay (2.48), work overload (2.39), the need to resolve unavoidable personal or family-related bureaucratic matters (2.38), the need for time for continuing education or postgraduate studies (2.30), lack of professional recognition (2.20), stress and anxiety (2.19), and demotivation (2.03). Conclusions: The primary reasons for absenteeism among nursing technicians are fatigue, low pay, and work overload. These factors are multifactorial in nature, and the perceived importance of each varies according to the professionals’ demographic profiles. The findings enable managers to plan and implement effective actions in education, prevention, and health surveillance, helping to adapt the work environment and reduce the risk of absenteeism.